Circulating biomarker responses to medical management vs. mechanical circulatory support in severe inotrope‐dependent acute heart failure. (24th November 2015) - Meredith, Anna J.; Dai, Darlene L. Y.; Chen, Virginia; Hollander, Zsuzsanna; Ng, Raymond; Kaan, Annemarie; Tebbutt, Scott; Ramanathan, Krishnan; Cheung, Anson; McManus, Bruce M.
Abstract: Background: Severe inotrope‐dependent acute heart failure (AHF) is associated with poor clinical outcomes. There are currently no well‐defined blood biomarkers of response to treatment that can guide management or identify recovery in this patient population. In the present study, we characterized the levels of novel and emerging circulating biomarkers of heart failure in patients with AHF over the first 30 days of medical management or mechanical circulatory support (MCS). We hypothesized a shared a plasma proteomic treatment response would be identifiable in both patient groups, representing reversal of the AHF phenotype. Methods and results: Time course plasma samples of the first 30 days of therapy, obtained from patients managed medically ( n = 8) or with implantable MCS ( n = 5), underwent semi‐targeted and candidate biomarker analyses, using multiple reaction monitoring (MRM) mass spectrometry, antibody arrays, and enzyme‐linked immunosorbent assays. Differentially expressed proteins were identified using robust limma for MRM and antibody array data. Patients managed medically or with implantable MCS had a shared proteomic signature of six plasma proteins: circulating cardiotrophin 1, cardiac troponin T, clusterin, and dickopff 1 increased, while levels of C‐reactive protein and growth differentiation factor 15 decreased in both groups over the 30 day time course. Conclusions: We have characterized the temporal proteomic signature of clinical recovery in AHF patients managed medically or with MCS, over the first 30 days of treatment. Changes in biomarker expression over the time course of treatment may provide a basis for understanding the biological basis of AHF, potentially identifying novel markers and pathophysiologic mechanisms of recovery.